PENDIDIKAN ISLAM (Pengertian, Ruang Lingkup dan Epistemologinya) - ., Mappasiara (Inspiratif Pendidikan, 2018)
Abstract: Islamic education can be defined as a process of providing guidance and instruction to learners in order to improve the potential quality of the faith, intellectual, personality and skills of learners. The knowledge imparted to learners based on Islamic teachings is a future investment. The scope of Islamic education encompasses all Islamic teachings integrated in belief (faith) and worship and muamalah whose implications affect the process of thinking, feeling, doing and the formation of personality which in turn manifested in akhlaq al-karimah as a form of Muslim man.